"My Life is More Important Than Family Honor:" Offline Protests, Counter‐Cyberactivism, and Article 308. Issue 1 (31st December 2020) - Tobin, Sarah A.
Abstract: In summer 2012, protests erupted in Jordan in light of several high-profile enactments of Article 308 of the Penal Code, or "Rape Law, " that allows rape charges to be dropped if the perpetrator agrees to marry the victim, which were organized offline and aimed to create a groundswell of public support for changing gender inequities in society rather than political and legal structures. Users of social media were quick to deride and disparage the protests and protesters in highly visible and aggressive ways. This case demonstrates that the Internet can simultaneously act as a vehicle for resisting social exclusion and gender segregation through cyberactivism, while also serving as a mechanism for reinforcing preexisting cultural norms through, what I call, "counter-cyberactivism." Such displays amplify the argument that the Internet serves as a space for online cultural performance of offline life, which enables the capacity for both cultural change and durability simultaneously. I conclude with the implications of this case for the online, virtual umma.